(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
In a relaxed dialogue, Pedro R. Ilgenfritz da Silva seeks to explain a little about the formation and performance of the stage lighting area in New Zealand. Michael Craven, your guest, talks about his beginnings in the field, since he was a sixteen-year-old student in a school class where, in addition to being an actor, he also received the task of being a set designer, and became fond of stage techniques and making lights. He then underwent scenic training and pursued a career as a lighting designer and multi-operator. He currently works as a professor and technical director in lighting at UNITEC in Auckland, New Zealand.